Comparative Analysis of Physicochemical and Pollen Characteristics of Honey from Different Regions in India - Alka Rani,; Sunita Verma, (The Bioscan, 2025)
This study evaluates the physicochemical properties and pollen composition of honey samples collected from Guwahati, Chennai, Bengaluru, and Madurai, India. Key quality parameters—including sucrose content, fructose-glucose ratio, moisture, total reducing sugar, hydroxymethylfurfural (HMF), diastase activity, and pollen count—were analyzed to assess honey authenticity and regional variations. Guwahati honey exhibited the highest moisture content (19.93%), while Chennai had the lowest (19.32%), ensuring better shelf stability. Bengaluru honey had the highest sucrose levels (2.0%), suggesting possible processing or filtration, whereas Guwahati and Madurai had significantly lower sucrose (0.5%), reinforcing their multifloral nature. Total reducing sugar content was highest in Madurai (79.67%) and Guwahati (78.63%), indicating richer floral diversity, while Bengaluru had the lowest (74.10%). Specific gravity was highest in Chennai (1.55) and lowest in Bengaluru (1.35), suggesting possible dilution or floral origin differences. HMF levels were statistically similar across all samples (60 mg/kg, p = 1.0000), indicating compliance with honey quality standards.